The pharmacokinetics and effects of meloxicam, gabapentin, and flunixin in postweaning dairy calves following dehorning with local anesthesia. Issue 6 (8th March 2013) - Glynn, H. D.; Coetzee, J. F.; Edwards‐Callaway, L. N.; Dockweiler, J. C.; Allen, K. A.; Lubbers, B.; Jones, M.; Fraccaro, E.; Bergamasco, L. L.; KuKanich, B.
Abstract : Approved analgesic compounds in cattle are not currently available in the United States due to the lack of validated pain assessment methods and marker residue depletion studies. In this study, we compared the pharmacokinetic parameters and effect of preemptive analgesics administered to calves subjected to dehorning with local anesthesia. Holstein steers were randomly assigned to receive one of the following treatments per os (PO) or intravenously (IV) ( n = 8/group): meloxicam (1 mg/kg PO), gabapentin (15 mg/kg PO), meloxicam (1 mg/kg), and gabapentin (15 mg/kg) PO, flunixin (2.2 mg/kg IV), or a placebo. Plasma drug, haptoglobin, substance P (SP) concentrations, serum cortisol concentrations, ocular thermography, mechanical nociceptive threshold (MNT), and average daily gain (ADG) were evaluated. Data were analyzed using mixed‐effects models and noncompartmental pharmacokinetic analysis. Meloxicam, gabapentin, and meloxicam with gabapentin at the present doses did not reduce cortisol concentrations. Analgesic‐treated calves had significantly lower plasma SP concentrations and improved ADG compared with controls. Flunixin calves had reduced circulating cortisol compared with controls. Meloxicam‐treated calves showed an increase in MNT at two horn bud sites compared with the other treatments. Analgesics improved ADG and reduced biomarkers of pain, but effects differed by compound and route of administration.